Refractory Thyroid Carcinomas: Experience of the Medical Oncology Department of Hassan II Hospital in Fez, Morocco - Nouiakh, Lamyae; Karima Oualla,; Ouahbi, Hajar; Berrad, Soumia; Erraichi, Hayat; Amaadour, Lamiae; Zineb Benbrahim,; Arifi, Samia; Meryem boubou,; Nawfel Mellas, (International Journal of Innovative Research in Medical Science, 2020)
Background: Refractory thyroid carcinomas are rare. The prognosis of these carcinomas depends on several factors including the histological type and the evolutionary stage. Aim: Determine the epidemiological, pathological and prognostic characteristics of refractory thyroid carcinomas and to focus on the therapeutic modalities used for the treatment of these cancers. Methods: Our work is a retrospective descriptive study on 28 cases collected in the medical oncology department of Hassan II hospital in Fez over a period of 7 years, from January 2012 to January 2019. The statistical analysis of the results was done by SPSS version 23. Survival was calculated by the Kaplan-Meier method. Results: The average age was 57.3 years, with a sex ratio F/M of 1.3. Thyroid nodule and multi-hetero nodular goiter were present in 32.1% and 28.5% of cases, respectively. The most common carcinoma was the papillary (36%) followed by the vesicular (25%), the anaplastic (25%) and the medullary (14%). The first line treatment was based on SORAFENIB (administered to 40% of patients) and on conventional chemotherapy (60%). After an average number of 4 courses, the objective response rate was 47%. The median of progression-free survival was 15 months and that of overall survival was 25 months. Conclusion: Overall, refractory thyroid cancers are rare. Systemic treatments have evolved considerably in recent years with the development of targeted therapies, pending the advent of immunotherapy that could improve the prognosis of patients with these cancers, particularly those with anaplastic carcinoma.